Analisis Limit Momen Pipa Elbow dengan Beban In-Plane Bending - Asnawi Lubis (JURNAL MECHANICAL, 2010)
Pipe bends or elbows are of important component in a piping system. In addition to its function for changing the direction of piping due to layout restriction, an elbow can accommodate expansion because it is more flexible than an equivalent straight pipe with the same material and dimension. However, and elbow can not be analyzed using the engineer theory of bending, because its cross-section become oval under bending. This paper reports a result of finite element study of bending behavior of a pipe elbow and its influence on limit moment. Limit moment was obtained using nonlinear analysis and Newton-Raphson algorithm was employed. Material behavior of pipe was treated as large strain, elastic-perfectly-plastic. The results show that a pipe elbow under in-plane opening bending is stiffer than those under in-plane closing bending, indicated by their limit load – 4.83 times yield stress for in-plane opening bending and 1.34 times the yield stress for in-plane closing bending. Keywords: pipe elbow, limit moment, nonlinear analysis, in-plane bending